Laser splintering method for improving consistency of crack propagation paths through recesses

By setting a depression on the surface of the crystal ingot and using laser control crack expansion, the problem of unstable cracks in laser cracks is solved, a more uniform and controllable cracking process is achieved, and the utilization rate and processing accuracy of the crystal ingot are improved.

CN119368910APending Publication Date: 2025-01-28BEIJING JINGFEI SEMICON TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411971999.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the laser lobe process, due to the instability of the crack starting point and expansion path, the crack propagation during the lobe process is uneven, and the phenomenon of offset and bifurcation occurs, resulting in waste of materials and reduced ingot utilization.

Method used

By setting a depression on the surface of the crystal ingot, and using laser irradiation depression to control the formation and expansion of the initial crack, to ensure the stable expansion of the crack along the scheduled direction, and reduce the production of irregular cracks.

Benefits of technology

Realize the reduction of crushing thickness, improve the utilization rate of crystal ingots, reduce waste of material, and significantly improve the accuracy and efficiency of laser cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368910A_ABST
    Figure CN119368910A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wafer processing, in particular to a laser splintering method for improving consistency of crack propagation paths through recesses, which comprises the following steps: preparing a crystal ingot, preparing the recesses, irradiating the recesses with first laser, and forming initial cracks in the crystal ingot. The pits are formed in the surface of the crystal ingot, formation and extension of initial cracks are controlled through laser irradiation on the pits, the polishing and grinding thickness is reduced, and the utilization rate of the crystal ingot is increased. Laser energy is concentrated by the recesses, and local high temperature and high stress are generated at deeper positions of the crystal ingot, so that initial cracks are generated at preset positions and extend along preset directions, crack paths are accurately controlled, and irregular cracks are reduced. By controlling the position and the direction of the crack, crack offset and forking are avoided, material waste is reduced, the crystal ingot utilization rate and the production efficiency are improved, and the precision, the efficiency and the product quality of the laser splitting process are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of wafer processing technology, and in particular to a laser cracking method for improving the consistency of crack propagation paths by recessing. Background Art

[0002] Compared with traditional mechanical splitting methods, laser splitting technology is a non-contact processing method that avoids the shortcomings of high material waste in traditional mechanical cutting. It can achieve higher precision, better surface quality, and higher processing efficiency, and has received widespread attention in the industry.

[0003] During the laser splitting process, a high-energy-density laser beam is concentrated inside the ingot, forming local high-temperature and high-stress areas. Specifically, the ingot material absorbs the laser energy to form a local high-temperature area; due to the thermal expansion effect, the local high-temperature area produces high stress concentration, thus forming an initial crack inside the ingot; by controlling the laser scanning path and parameters, the crack is accurately guided to expand in a predetermined direction, thereby achieving a uniform and controllable splitting effect.

[0004] Although laser cracking technology has significant advantages, in actual applications, due to the instability of the crack starting point and expansion path, the crack expansion during the cracking process is uneven, and there are phenomena such as offset and bifurcation. This irregular crack requires more wafer thickness to be polished away during subsequent polishing, resulting in a large amount of material waste and reducing the utilization rate of the ingot. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a laser cracking method for improving the consistency of crack propagation path by recessing, comprising the following steps: Step 1: Prepare the ingot; Step 2, preparing a depression; Step 3: applying a first laser to irradiate the depression to form an initial crack in the ingot.

[0006] The present invention achieves the purpose of reducing the polishing thickness and improving the utilization rate of the crystal ingot by setting a depression on the surface of the crystal ingot and using laser to irradiate the depression to control the formation and expansion of the initial crack. Specifically, the depression set on the surface of the crystal ingot effectively concentrates the laser energy, generating local high temperature and high stress deeper in the crystal ingot. This stress concentration causes the initial crack to initiate at a predetermined position and expand along a predetermined direction, thereby accurately controlling the crack path and reducing the generation of irregular cracks; by controlling the position and direction of the initial crack, it is ensured that the crack expands along the optimal path, avoiding irregular phenomena such as crack offset and bifurcation, reducing material waste caused by irregular cracks, and improving the utilization rate of the crystal ingot. In other words, the splitting process is more uniform and controllable, reducing the thickness of excess material that needs to be removed by polishing, and improving material utilization.

[0007] Furthermore, step 1 includes polishing the ingot, and obtaining a flat and clean ingot surface through polishing provides a good foundation for the subsequent laser splitting process. In addition, polishing the ingot also prepares for the subsequent step of preparing a uniform diameter and uniform depth of the concave.

[0008] Furthermore, in step 2, a laser etching method is applied to form a depression on the surface of the ingot. Methods for preparing depressions on the surface of the ingot include photolithography and chemical etching, mechanical processing, focused ion beam etching and laser etching. Laser etching is to focus a high-precision laser beam on the surface of the ingot and use high energy density to vaporize or ablate the material to form a depression of the desired shape. Laser etching has the advantages of high precision and high resolution, non-contact processing, and no pollution. The prepared depression can ensure that the starting point and expansion path of the crack in the subsequent laser splitting process are accurately controlled, thereby improving the utilization rate of the ingot and the quality of the wafer. These advantages make laser etching the preferred method for preparing depressions.

[0009] Furthermore, the shape of the depression is conical. The geometric shape of the conical depression helps to concentrate the laser energy at the bottom of the depression, thereby forming a high energy density area inside the ingot. This energy concentration effect helps to produce a high stress area at the bottom of the depression and inside the ingot, inducing cracks; at the same time, the conical depression also effectively reduces the reflection and scattering of the first laser on the surface, improves the energy utilization efficiency, and allows more laser energy to act on the inside of the ingot. At the same time, the tip of the conical depression provides a clear stress concentration point, allowing the crack to initiate from a predetermined position, which helps to control the initial position and direction of the crack and reduce the uncertainty of crack propagation.

[0010] Furthermore, the diameter of the depression is greater than 2 microns and less than 4 microns, and the depth of the depression is greater than 2 microns and less than 4 microns. The depression of appropriate size not only realizes the concentration of laser energy and produces clear microcracks, but also in the subsequent polishing, only a thin thickness needs to be polished away, reducing material waste.

[0011] Furthermore, in step 3, the first laser is an ultrashort pulse laser, and the pulse width of the first laser is picoseconds or sub-picoseconds or femtoseconds. The pulse of the picosecond or femtosecond laser is extremely short, and the energy is concentratedly released in an extremely short time. The extremely high time resolution allows the heating process of the material to be completed in a very short time, and the heat has no time to diffuse to the surrounding area, thereby reducing the heat-affected zone, avoiding large-area thermal damage, and improving the processing accuracy. In other words, the ablation threshold of the material is reached in an instant, resulting in a fine processing effect, and effectively guiding the crack to initiate from a predetermined position. Due to the small heat-affected zone, the material deformation caused by thermal stress and the accumulation of thermal stress during crack propagation are reduced, ensuring that the crack stably propagates in a predetermined direction.

[0012] Furthermore, the spot size of the first laser is smaller than the diameter of the depression. The spot size of the first laser is smaller than the diameter of the depression, ensuring that the laser energy can be completely concentrated inside the depression without being dispersed to the external area, which helps to form a higher temperature and stress concentration area at the bottom of the depression, and promotes the initiation of initial cracks at a predetermined position.

[0013] Furthermore, after step 3, a second laser is applied to irradiate the depression to extend the initial crack in the ingot. The main function of the second laser is to further extend the initial crack formed by the first laser. By controlling the parameters of the second laser (such as power, pulse width and scanning speed), it can be ensured that the crack further extends in a predetermined direction to achieve a complete cracking process.

[0014] Furthermore, the wavelength of the second laser is greater than that of the first laser. The first laser has a shorter wavelength, and a short-wavelength laser has a higher energy density and a higher absorption efficiency, and its heat-affected zone is also small, which reduces thermal stress and thermal damage. The second laser has a longer wavelength, and a longer-wavelength laser is more suitable for heating and guiding crack propagation. Preferably, the second laser is an infrared laser, which has better material penetration ability, can provide a more uniform thermal effect, and help the crack to stably propagate along a predetermined path.

[0015] Beneficial effects of the present invention: The present invention reduces the polishing thickness and improves the utilization rate of the ingot by setting a depression on the surface of the ingot and controlling the formation and expansion of the initial crack by irradiating the depression with a laser. The depression concentrates the laser energy, generates local high temperature and high stress deeper in the ingot, causes the initial crack to initiate at a predetermined position and expand in a predetermined direction, accurately controls the crack path, and reduces the generation of irregular cracks. By controlling the crack position and direction, crack deviation and bifurcation are avoided, material waste is reduced, the utilization rate and production efficiency of the ingot are improved, and the accuracy, efficiency and product quality of the laser cleaving process are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the laser splitting method that uses depressions to improve the consistency of crack propagation paths. DETAILED DESCRIPTION

[0017] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below with reference to the accompanying drawings and examples.

[0018] The present invention provides a laser cracking method for improving the consistency of crack propagation path by recessing, such as Figure 1 As shown, the process includes three steps. To clearly illustrate the present invention, taking the splitting of silicon carbide ingot as an example, the three steps are described as follows: Step 1: Prepare the ingot.

[0019] This step includes polishing the ingot, cleaning the ingot, and inspecting the surface of the ingot. Rough and fine grinding are used to remove surface defects and unevenness to obtain a flat and smooth surface without obvious scratches, cracks, and other impurities on the surface of the ingot. Grinding particles and polishing liquid may remain on the surface of the ingot after polishing. Use an ultrasonic cleaner combined with deionized water to remove surface residues to ensure that the surface of the ingot is clean. Inspecting the surface of the ingot is used to determine whether there are microcracks, scratches, and other defects on the surface of the ingot.

[0020] Step 2: Prepare a depression.

[0021] In this step, the femtosecond laser is focused on the surface of the ingot, and a high-precision microscope or laser alignment system is used to align the focus with the predetermined etching position. The power of the femtosecond laser is greater than 0.5 watts and less than 2 watts, the pulse width is between 10 and 100 femtoseconds, the repetition frequency of the laser pulse is between 1KHz and 500KHz, and the laser wavelength is between 800 nanometers (titanium sapphire laser) and 1030 nanometers (Yb fiber laser). Start the femtosecond laser and etch according to the preset scanning path, with a scanning speed between 10mm / s and 100mm / s. The laser pulse energy is between 20 nanojoules and 400 nanojoules. The laser pulse generates extremely high instantaneous temperature and pressure on the surface of the ingot, causing the material to vaporize and dissociate instantly to form a depression. Through multiple scans, the material is removed layer by layer until the desired depression depth and shape are reached. In the present application, the shape of the depression is conical, the diameter of the depression is greater than 2 microns and less than 4 microns, and the depth of the depression is greater than 2 microns and less than 4 microns. During preparation, the top surface diameter of the conical depression is 4 microns, and the diameter of the femtosecond laser spot is 2 microns. The femtosecond laser spot is moved within the top surface of the conical depression, and the center of the cone is irradiated for a long time, and more material is removed, forming a conical shape. After etching, the surface of the ingot should be cleaned with deionized water to remove particles and residues generated during the processing.

[0022] Step 3: Apply a first laser to irradiate the depression to form an initial crack in the ingot.

[0023] The wavelength of the first laser is 532 nanometers, the laser power is 0.1 to 1 watt, the pulse width is 30 to 50 femtoseconds, the repetition frequency is 100KHz to 500KHz, the spot size is 1 micron to 3 microns, the scanning speed is 10mm / s to 50mm / s, and the pulse energy is 20 nanojoules to 200 nanojoules. When the 532-nanometer femtosecond laser is irradiated onto the surface of the silicon carbide ingot, the ingot material absorbs the laser energy. Since the pulse time of the femtosecond laser is extremely short, the energy is instantly concentrated at the bottom of the depression. The high-intensity femtosecond laser pulse causes a multi-photon absorption process inside the silicon carbide crystal, produces a photoionization effect, forms a plasma, and the plasma expands rapidly, generating local high temperatures, causing thermal expansion of the material. The surrounding cooled material limits this expansion, forming a huge thermal stress concentration. Especially at the bottom of the depression, due to the limiting effect of the depression, the thermal effect is concentrated there. In the area of ​​high stress concentration, tiny defects in the crystal structure (such as dislocations, grain boundaries, etc.) are activated, which is called the starting point of crack initiation. When the local stress exceeds the fracture strength of the silicon carbide material, microcracks begin to initiate at the bottom of the depression. The formation of the initial crack further releases the local stress, but due to continuous laser irradiation and thermal stress, the crack continues to expand inside the material. Since the pulse time of the femtosecond laser is extremely short, the laser energy disappears quickly, and the plasma cools down. During the cooling process, the initial crack stops expanding and forms a stable microcrack. In the present invention, the geometric shape of the depression helps to concentrate the energy of the femtosecond laser at the bottom of the depression, improve the local energy density, and enable the laser to generate a higher local temperature in a smaller volume; the presence of the depression makes the thermal expansion effect more concentrated and controllable, generating highly concentrated thermal stress, which promotes the initiation of microcracks; the bottom of the depression naturally becomes a stress concentration point, and under the action of the first laser, the high temperature and high pressure in the local area cause the stress in the material to increase rapidly, and the stress concentration effect at the bottom of the depression further amplifies this stress; in the stress concentration area, micro defects in the crystal structure are more easily activated, which is called the starting point of crack initiation, thereby forming an initial crack with high consistency; the shape of the depression avoids crack deviation and bifurcation, ensures that the crack expands along the optimal path, reduces the generation of irregular cracks, and thus improves the quality of the cracks.

[0024] Preferably, after step 3, it also includes applying a second laser to irradiate the depression to expand the initial crack in the ingot. The wavelength of the second laser is 1064 nanometers, which can more efficiently transfer energy to the inside of the ingot, thereby promoting the expansion of the crack. That is to say, the 1064-nanometer laser wavelength is longer and has stronger penetration ability, which can produce a uniform heating effect inside the material, which is conducive to the stable expansion of the crack along the predetermined path. The laser power is 0.5 to 3 watts, the pulse width is 20 nanoseconds to 50 nanoseconds, the repetition frequency is 10KHz to 30KHz, the spot size is 20 microns to 40 microns, the focus is located at the front end of the initial crack, the scanning speed is 5mm / s to 15mm / s, and the pulse energy is 50 microjoules to 200 microjoules. When the second laser (with a wavelength of 1064 nanometers) irradiates the depression, its energy is effectively absorbed by the silicon carbide ingot, producing a uniform thermal effect. The laser energy is converted into heat inside the ingot, causing the local area at the bottom of the depression and the front end of the initial crack to heat up rapidly. High temperatures cause thermal expansion of the material, creating additional stress concentration areas. Due to the long wavelength of the laser, the thermal effect penetrates deep into the material, causing the crack to extend smoothly along a predetermined path. The repetitive action and scanning motion of the laser pulse further guide the crack to extend evenly, avoiding local overheating and the generation of new cracks. During the cooling stage, the extended crack stabilizes, forming a highly consistent splinter path, thereby improving the splinter quality and processing accuracy.

[0025] In summary, the present invention achieves efficient splitting by setting a depression on the surface of the ingot and applying laser irradiation to precisely control the formation and expansion of the initial crack. First, the depression is irradiated with an ultrashort pulse laser to concentrate energy at the bottom of the depression, generate local high temperature and high stress, and induce initial cracks. Subsequently, a long-wavelength laser is used to further irradiate the depression, uniformly heat and guide the crack to expand along a predetermined path. This method optimizes laser parameters and depression design to ensure the consistency and stability of the crack path, reduce irregular cracks and material waste, improve ingot utilization and splitting quality, and significantly improve processing accuracy and production efficiency. It has good application prospects in the field of wafer processing technology.

[0026] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A laser cracking method for improving the consistency of crack propagation path by concave cutting, characterized in that: The steps include: Step 1: Prepare the ingot; Step 2, preparing a depression; Step 3: applying a first laser to irradiate the depression to form an initial crack in the ingot.

2. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 1, characterized in that: The step 1 includes polishing the ingot.

3. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 2, characterized in that: In step 2, the recess is formed on the surface of the ingot by using a laser etching method.

4. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 3, characterized in that: The shape of the depression is conical.

5. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 4, characterized in that: The diameter of the depression is greater than 2 micrometers and less than 4 micrometers.

6. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 5, characterized in that: The depth of the depression is greater than 2 micrometers and less than 4 micrometers.

7. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 6, characterized in that: In step 3, the first laser is an ultrashort pulse laser, and the pulse width of the first laser is picosecond, sub-picosecond or femtosecond.

8. The laser cracking method for improving the consistency of crack propagation path by depression according to any one of claims 1 to 7, characterized in that: The spot size of the first laser is smaller than the diameter of the recess.

9. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 8, characterized in that: After step 3, the method further includes applying a second laser to irradiate the recess to extend the initial crack in the ingot.

10. The laser cracking method for improving the consistency of crack propagation path by recessing as claimed in claim 9, characterized in that: The wavelength of the second laser is greater than the wavelength of the first laser.

Citation Information

Cited By

  • Laser processing method of ceramic substrate

    CN120326128A

  • Laser processing method for ceramic substrate

    CN120326128B